KEDUDUKAN HUKUM DAN AKIBAT HUKUM PERJANJIAN JUAL BELI TANAH YANG TIDAK DICATATKAN DI KANTOR PERTANAHAN DI INDONESIA - Luverne Pujian Quinn; Gunawan Djajaputra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study examines the legal standing and validity of land sale-purchase agreements that are not registered with the Land Office, as well as the legal consequences for the contracting parties and third parties. In Indonesia’s legal system, land transactions operate under two distinct regimes: civil law, governed by Articles 1320 and 1338 of the Civil Code, and agrarian law, regulated by the Basic Agrarian Law (UUPA) and Government Regulation No. 24 of 1997. From a civil law perspective, an underhand sale-purchase agreement remains valid as long as it fulfills the requirements of consent, legal capacity, a specific object, and a lawful cause. However, such an agreement only creates an obligatoir effect and does not transfer property rights until an official Sale and Purchase Deed (AJB) is executed before a PPAT and registered with the Land Office. Consequently, buyers face legal vulnerability regarding third-party claims and lack full legal protection. In certain cases, such as the Subang District Court decision, long-term possession, proof of payment, and the absence of objection by the seller can strengthen the buyer’s position to apply for a land certificate. Nonetheless, registration remains essential to ensuring legal certainty and protecting third-party interests.